Analisis Pertumbuhan Ekonomi Indonesia pada Periode Kebijakan Fiskal (2020–2024) Menggunakan K-Means Clustering - Rafael Grealdi Sinaga; Marta Rahmawati Purba; Sardo Pardingotan Sipayung (GLOBAL SCIENTS PUBLISHER, 2026)
Economic growth is one of the main indicators in assessing the success of a country's fiscal policy. In the modern fiscal policy period, Indonesia's economic growth shows different dynamics across regions. This study aims to analyze Indonesia's economic growth patterns using the K-Means Clustering method. The data used in this study are sourced from the Indonesian Regional Data Management Information System (SIMREG) for the 2020–2024 period, with variables including Gross Domestic Product (GDP) growth rate, poverty rate, and poverty rate. The K-Means method is used to group regions based on similar economic growth characteristics. The results show the formation of three main clusters: regions with high, medium, and low economic growth. Each cluster has different economic characteristics, reflecting growth inequality between regions in Indonesia. This research is expected to serve as evaluation material and reference for the government in planning more targeted fiscal policies and encouraging equitable economic growth in Indonesia.